Photochemical Rearrangements in Heterocyclic Chemistry. Issue 10 (15th October 2019) - Lefebvre, Corentin; Fortier, Lucas; Hoffmann, Norbert
Abstract : Heterocyclic compounds play an important role in many domains of chemistry. They are important structural elements in bioactive compounds. Photochemical reactions enable transformations of such compounds in a very convenient way. In many cases no chemical reagent is used. Members of one compound family can be transformed into members of another one. Three important types of photochemical rearrangements with heterocyclic compounds are discussed: Photochemical heteroatom isomerization involving heteroatoms and substituents, photochemical reactions involving hydrogen atom transfer (HAT) and photochemical electrocyclization. Abstract : Photochemical rearrangements of heterocycles involving heteroatom isomerization, hydrogen atom transfer, or electrocyclization are convenient tools in heterocyclic chemistry to generate a large structural diversity.